Deciphering the potential of plant metabolites as insecticides against melon fly (Zeugodacus cucurbitae): Exposing control alternatives to assure food security - Zinat Jahan Chowdhury; Anik Banik; Tanjin Barketullah Robin; Mohammed Rashed Chowdhury (Heliyon)
In the absence of effective biological or chemical controls, the melon fly poses a significant threat to food security, particularly impacting cucurbit crops in tropical and subtropical regions. Melon fly infestations have resulted in yield losses of 30 %–100 %, depending on the specific cucurbit species and season. Current control methods using synthetic chemicals are challenging due to their environmental and biological impacts. This study identified 59 phytocompounds with potential insecticidal properties against the melon fly, exhibiting minimal environmental impact. Key protein targets—hedgehog protein, spastin protein, and ABC-type heme transporter ABCB6 protein—were selected for binding affinity analysis. Camptothecin demonstrated the highest binding affinities for hedgehog protein (−57.32 kcal/mol) and spastin protein (−50.84 kcal/mol), while jervine had the strongest binding affinity for ABC-type heme transporter ABCB6 protein (−43.92 kcal/mol). The control compound, malathion, showed lower binding affinities across all three proteins. Stability of the top compound-protein complexes was further confirmed through a 100 ns molecular dynamics simulation. In insecticide-likeness evaluations, jervine consistently scored high, with camptothecin also performing well, while neriifolin ranked lower. The leading compounds showed no adverse effects that could diminish their insecticidal potential. These findings indicate that jervine and camptothecin are promising candidates for melon fly management, offering potential to prevent significant crop losses. However, as this study was conducted solely through computational methods, we recommend subsequent in vitro and field trials for the future drug development.